Differential Tropism and Replication Kinetics of Human Immunodeficiency Virus Type 1 Isolates in Thymocytes: Coreceptor Expression Allows Viral Entry, but Productive Infection of Distinct Subsets Is Determined at the Postentry Level - Pedroza-Martins, Livia (American Society for Microbiology, 1998)
Human thymocytes are readily infected with human immunodeficiency virus type 1 (HIV-1) in vivo and in vitro. In this study, we found that the kinetics of replication and cytopathic effects of two molecular isolates, NL4-3 and JR-CSF, in postnatal thymocytes are best explained by the distribution of chemokine receptors used for viral entry. CXCR4 was expressed at high levels on most thymocytes, whereas CCR5 expression was restricted to only 0.1 to 2% of thymocytes. The difference in the amount of proviral DNA detected after infection of fresh thymocytes with NL4-3 or JR-CSF correlated with the levels of CXCR4 and CCR5 surface expression. Anti-CCR5 blocking studies showed that low levels of CCR5 were necessary and sufficient for JR-CSF entry in thymocytes. Interleukin-2 (IL-2), IL-4, and IL-7, cytokines normally present in the thymus, influenced the expression of CXCR4 and CCR5 on thymocytes and thus increased the infectivity and spread of both NL4-3 and JR-CSF in culture. NL4-3 was produced by both immature and mature thymocytes, whereas JR-CSF production was restricted to the mature CD1(−)/CD69(+) population. Although CXCR4 and CCR5 distribution readily explained viral entry in mature CD69(+) and immature CD69(−) cells, and correlated with proviral DNA distribution, we found that viral production was favored in CD69(+) cells. Therefore, while expression of CD4 and appropriate coreceptors are essential determinants of viral entry, factors related to activation and stage-specific maturation contribute to HIV-1 replication in thymocyte subsets. These results have direct implications for HIV-1 pathogenesis in pediatric patients.